The Influence of Use of Rupintive Media on Literation of Group B Children In Ra Ar-Roudhloh Tenggaro Keluang District, Musi Banyuasin District - Dessi Andriani; Miftahul Jannah (Departement of Mathematics Education, 2023)
This study aims to determine whether there is an influence of RUPINTIF media on the literacy of group B children at RA Ar-Roudhloh Tenggaro, Keluang District, Musi Banyuasin Regency. The problem that researchers encountered in this study was the effect of using RUPINTIF media on group B literacy at RA Ar-Roudhloh Tenggaro, Keluang District, Musi Banyuasin Regency. This research method is a Pre-Experimental Design (Non-Design) with the form of a One-Group Pretest-Posttest design. The population is 15 children and the research sample is 10 children. Data collection techniques for this research are observation, interviews, and documentation. Based on the results of research and discussions that have been conducted by researchers, it shows that the use of RUPINTIF media has an influence on literacy in group B children at RA Ar-Roudhloh Tenggaro. RUPINTIF media playing activities can improve literacy skills because in this game children can play with fun and can also recognize letters into syllables and can arrange letters to make it easier for children. Based on the posttest data obtained 96.5 (very suitable) then the pretest data obtained was 64.2 (not appropriate). This shows that RUPINTIF media has a significant effect on literacy in group B children at RA Ar-Roudhloh Tenggaro. Then testing this hypothesis has the effect of RUPINTIF media on children's literacy in group B at RA Ar-Roudhloh Tenggaro.